THE LEADERSHIP MODEL OF KH IMAM BARMAWI BURHAN IN PRESERVING ISLAMIC TRADITIONS - Abd Salam; Akhmadi; Rifa'i; Roma Wijaya (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
This study aims to analyze the leadership model of KH Imam Barmawi Burhan (KHIBB) in preserving Islamic traditions at PPI Nurul Burhan. This research employs a qualitative approach with a case study design to obtain an in-depth understanding of leadership practices within the pesantren context. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using an interactive analysis model consisting of data reduction, data display, and systematic conclusion drawing. The findings reveal four key elements of KHIBB’s leadership model in preserving Islamic traditions at PPI Nurul Burhan: (1) the model of preserving Islamic traditions; (2) strategies for maintaining Islamic traditions amid modernization; (3) the utilization of technological media in disseminating Islamic traditions; and (4) the formation of students’ Islamic character. In terms of the preservation model, KHIBB emphasizes religious routines, including congregational prayers, veneration of the Qur’an, and the recitation of shalawat. This leadership model demonstrates the integration of preserving religious traditions, adapting to technological developments, and fostering moderate religious character among students. This study contributes to the development of Islamic educational leadership studies by highlighting the crucial role of kiai leadership in sustaining Islamic traditions within pesantren while maintaining their relevance in the face of contemporary societal changes. Keywords: kiai leadership, preservation of Islamic traditions, pesantren, Islam Nusantara, Ahlussunnah wal Jamaah   Abstrak Penelitian ini bertujuan untuk menganalisis model kepemimpinan KHIBB dalam melestarikan tradisi Islam di PPI Nurul Burhan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus untuk memperoleh pemahaman yang mendalam mengenai praktik kepemimpinan dalam konteks pesantren. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi, kemudian dianalisis menggunakan model analisis interaktif yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan secara sistematis. Hasil penelitian menunjukkan bahwa terdapat empat unsur model kepemimpinan KHIBB dalam melestarikan tradisi Islam di PPI Nurul Burhan, yakni 1) model pelestarian tradisi Islam; 2) strategi dalam menjaga kelestarian tradisi Islam di tengah modernisasi; 3) pemanfaatan media teknologi dalam menyiarkan tradisi Islam; dan 4) pembentukan karakter Islami. Dalam konteks model pelestarian tradisi Islam, KHIBB menkankan rutinitas, yakni sholat berjama’ah, mengangungkan Al-Qur’an, dan pembacaan sholawat. Model kepemimpinan ini memperlihatkan integrasi antara pelestarian tradisi keagamaan, adaptasi terhadap perkembangan teknologi, dan pembentukan karakter religius yang moderat. Penelitian ini berkontribusi pada penguatan kajian kepemimpinan pendidikan Islam dengan menegaskan pentingnya peran kepemimpinan kiai dalam menjaga keberlanjutan tradisi Islam di pesantren sekaligus menjadikannya tetap relevan dalam menghadapi perubahan zaman. Kata kunci: kepemimpinan kiai, pelestarian tradisi Islam, pesantren, Islam Nusantara, Ahlussunnah wal Jamaah